Students’ Problem of using Youtube video as English Learning Media During Covid-19 Pandemic - Anwar Jumma Khotibi; Muhamad Sofian Hadi (Jurnal Studi Guru dan Pembelajaran, 2022)
This study aims to analyze the students’ problems in using Youtube videos as online English learning media during covid-19 pandemic at grade XI of SMK Al-Hasra. The research subject consists of 15 students of XI grade SMK Al-Hasra. The data are collected using qualitative research methods, namely the type of basic interpretive studies where the data are obtained by questionnaire to the student in the Google form. The result of data analysis showed that 73% of the student agree that the use of Youtube video as English Learning media has a problem that is need to fix in order to create the learning activity more excellent. Based on the research result of this study, the use of Youtube as online learning media need some enhancement in order to make online learning using Youtube even more effective.